2008
DOI: 10.3382/ps.2007-00526
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Cytokine Response of Commercial Source Broiler Chicks to Salmonella Typhimurium Infection

Abstract: Development of molecular-based immunotherapeutic strategies for controlling Salmonella Typhimurium (ST) infection in poultry requires a better understanding of intestinal and cecal cytokine responses. Accordingly, an experiment was conducted to measure changes in intestinal cytokine expression when commercial source broiler chickens were challenged with a nalidixic acid-resistant ST. Ross broiler chicks were nonchallenged with ST (control treatment) or challenged by orally giving 7.8 x 10(6) cfu at 4 d of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 75 publications
(83 reference statements)
4
31
0
Order By: Relevance
“…Moreover, the same study found that S. Typhimurium infection results in a pronounced heterophil influx to the cecal lamina propria and liver. It has also been shown that IL-1␤ mRNA was upregulated in the cecum at day 5 after oral infection with S. Typhimurium (13). In both organs the expression of the chemokine CXCLi2 along with the proinflammatory cytokine IL-1␤ is indicative of an early inflammatory response (51).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the same study found that S. Typhimurium infection results in a pronounced heterophil influx to the cecal lamina propria and liver. It has also been shown that IL-1␤ mRNA was upregulated in the cecum at day 5 after oral infection with S. Typhimurium (13). In both organs the expression of the chemokine CXCLi2 along with the proinflammatory cytokine IL-1␤ is indicative of an early inflammatory response (51).…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, induction may also be a result of the release of bacterial pathogen-associated molecular patterns (PAMPs), such as lipopolysaccharide, peptidoglycan, or flagellin, from the cecum into the circulatory system, followed by filtering through the hepatic portal system or clearance by the reticuloendothelial system (15,44). In chickens, the innate immune response to S. Typhimurium infections is induced by the production of inflammatory cytokines and chemokines, including IL-1, IFN-␥, IL-6, TGF-␤4, and CXCLi2, in in vitro and in vivo models (7,13,52). However, these studies mainly used WT strains for their analyses, despite the fact that induction of the innate immune response may be needed to protect chickens before the induction of the specific immune response (52).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there are marked changes in the expression of cytokines in response to ST infection in chickens with increased expression of the following: IL-1 beta in the jejunum, ileum and caeca; IL-6 in the jejunum and ileum and IFNγ in the ileum (Fasina et al, 2008). Moreover, there is increased expression of cytokines -IL-1beta, IL-8 and K203 in the intestine of newly hatched chicks in the presence of feed and bacteria (Bar-Shira and Fridman, 2006).…”
Section: Gastro-intestinal Immune Functioning and Responses To Bactermentioning
confidence: 98%
“…colonize most specifically the ceca and cecal tonsils (Crhanova et al, 2011) and S. Typhimurium infection induces proinflammatory cytokines IL-1␤ and IL-6 in the intestinal tissues of chickens (Fasina et al, 2008). We therefore monitored duIL-17A and duIL-17F transcript levels in the cecal tonsil of Salmonella-infected ducks.…”
Section: Quantitative Analysis Of Duil-17a and Duil-17f Mrna Expressimentioning
confidence: 99%